Determining timber volume of eucalyptus stands by airborne laser scanning - Oliveira, Luciano Teixeira de; Ferreira, Maria Zélia; Carvalho, Luis Marcelo Tavares de; Ferraz Filho, Antônio Carlos; Oliveira, Thomaz Chaves de Andrade; Silveira, Eduarda Martiniano de Oliveira; Acerbi Junior, Fausto Weimar (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the possibility of estimating the diameter at breast height (DBH) with tree height and number data derived from airborne laser scanning (LiDAR, light detection and ranging) dataset, and to determine the timber volume of an Eucalyptus sp. stand from these variables. The total number of detected trees was obtained using a local maxima filtering. Plant height estimated by LiDAR showed a nonsignificant tendency to underestimation. The estimate for DBH was coherent with the results found in the forest inventory; however, it also showed a tendency towards underestimation due to the observed behavior for height. The variable number of stems showed values close to the ones observed in the inventory plots. LiDAR underestimated the total timber volume in the stand in 11.4%, compared to the total volume delivered to the industry. The underestimation tendency of tree height (5% mean value) impacted the individual tree volume estimate and, consequently, the stand volume estimate. However, it is possible to obtain regression equations that estimate DBH with good precision, from the LiDAR plant height derived data. The parabolic model is the one that provides the best estimates for timber volumetric yield of eucalyptus stands.